Do Demographic Factors Contribute to Forced Vital Capacity Value of Covid-19 Survivors’ Lung Function? - Pertiwi, Harizza; Wulandari, Shenda Maulina; Rahmawati, Apriana; Rohmah, Ulfa Nur (Jurnal Kesehatan - STIKes Prima Nusantara, 2023)
Background: Aging can cause increased work of breathing and decreased respiratory muscle strength. Furthermore, males and females have different measures of lung function. This alone can become a reason for decreased lung function, especially if there is a history of Covid-19 infection which can cause further damage to the lungs. Purpose: This study investigates the correlation between age and sex differences in the Forced Vital Capacity value of Covid-19 survivors. Method: Using a cross-sectional design with a survey and observational method, this study involved 46 participants that were selected purposively based on their history of being positively diagnosed Covid. Data was collected using a questionnaire and observational form to collect data from the spirometer, then analyzed with the Pearson test and Independent Sample T-test. Result: The result shows that age (mean = 40,89) does have a significant correlation to FVC (mean = 2.3602), with p-value = 0,017 (< 0,05). On the contrary, sex difference does not have a significant correlation with FVC value, with p-value = 0,109 (>0,05). Conclusion: This study reveals that aging can further affect the lung function of Covid-19 survivors, especially when comorbid factors are involved. Moreover, both males and females have the same risk of decreased lung function after being infected by the Covid-19 virus. However, other factors may influence the lung function of Covid-19 survivors. Further research needs to be conducted to scrutinize those other factors.